2018
DOI: 10.11114/jets.v6i11a.3799
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Learning Tendencies of Teacher Candidates Studying in Pedagogical Formation Program

Abstract: The purpose of this research is to determine the lifelong learning tendencies of the teacher candidates who are studying in the pedagogical formation program and to compare them according to various variables. In the research, the following questions have been answered: 1. What is the level of life-long learning tendencies of prospective teachers in the pedagogical formation program? 2. Does the lifelong learning tendencies of students in the pedagogical formation program differ significantly by gender, depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The results obtained from the analysis of the quantitative data showed that students with lifelong learning skills should actively engage in learning, set their goals, have good communication skills, have basic literacy and numeracy skills, make researches, develop a set of organization skills, have improved social skills, have the capacity to embrace changes and demonstrate specific personal attributes that contribute to their capacity as lifelong learners. Solmaz (2017) and Gökyer et al (2018) found that lifelong learning tendencies of pre-service teachers were at high level. On the contrary, Özen and Öztürk (2016) found that lifelong tendencies of pre-service teachers were at moderate level.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 99%
“…The results obtained from the analysis of the quantitative data showed that students with lifelong learning skills should actively engage in learning, set their goals, have good communication skills, have basic literacy and numeracy skills, make researches, develop a set of organization skills, have improved social skills, have the capacity to embrace changes and demonstrate specific personal attributes that contribute to their capacity as lifelong learners. Solmaz (2017) and Gökyer et al (2018) found that lifelong learning tendencies of pre-service teachers were at high level. On the contrary, Özen and Öztürk (2016) found that lifelong tendencies of pre-service teachers were at moderate level.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 99%
“…Although the term lifelong learning started to be frequently used towards the end of the 1960s as a result of the world crisis in education (Barros 2012), it was first presented as a key concept in educational restructuring by Paul Lengrand at the sixteenth session of the UNESCO General Conference in 1970 (Gökyer et al 2018;Lengrand 1970). Since then, lifelong learning has become a challenging term in the educational policy of the European Union (Lee et al 2008), which declared 1996 as the year of lifelong learning by stressing its importance for a learning society (Knapper and Cropley 2000).…”
Section: Lifelong Learningmentioning
confidence: 99%